Supercritical Carbon Dioxide as the Sweep Fluid Always Enhance Solid-State Polymerization of Poly(bisphenol A carbonate) ? - Kim, Jaehoon; George W. Roberts; Douglas J. Kiserow; Kim, Jae Duck (Asian Society of Supercritical Fluids, 2007)
Effects of supercritical carbon dioxide (scCO2) as the sweep fluid on solid-state polymerization (SSP) of poly(bisphenol A carbonate) (BPA-PC) were investigated. Prepolymers with two different number average molecular weights, PCP6C (Mn = 3,800 g/mol) and PCP9C (Mn = 2400 g/mol), were synthesized using melt-transesterification. SSP of the prepolymers was carried out at reaction temperatures in the range 150-190 oC with scCO2 and N2 as the sweep fluids. Melting temperatures (Tm) and the heat of fusion (？H) were measured using differential scanning calorimetry (DSC), and crystallinity and the lamellar thickness of the solid-state synthesized polymers were estimated using the melting isotherms. It was found that scCO2 enhanced or diminished the SSP rate, depending on the prepolymer molecular weights. When the high molecular weight prepolymer (PCP6C) was used, scCO2 effectively plasticized the amorphous region of the polymer, thus significantly increased the SSP reaction rate by increasing chain mobility and facilitating condensate removal. When the low molecular weight prepolymer (PCP9C) was used, scCO2 significantly increased crystallinity, lamellar thickness of the polymer, thus decreased the SSP reaction rate by decreasing chain mobility and by retarding condensate removal. In addition, a larger amount of inactive end-groups were observed in the polymers synthesized from PCP9C. At 190 oC, BPA-PC with high absolute weight average molecular weight of 21,000 g/mol was obtained when scCO2 was used as the sweep fluid.
Keywords: supercritical carbon dioxide; Poly(bisphenol A carbonate); Solid-state polymerization